1968
DOI: 10.1002/cber.19681010837
|View full text |Cite
|
Sign up to set email alerts
|

Borimide, IV. Die Reaktion von Borimiden mit Phenylacetylen

Abstract: Pentafluorphenylbor‐[p‐methoxy‐phenylimid], C6F5B  NC6H4OCH3 (1), reagiert mit Phenylacetylen zu 6‐Methoxy‐4‐phenyl‐2‐pentafluorphenyl‐2.1‐borazaronaphthalin (6‐Methoxy‐4‐phenyl‐2‐pentafluorphenyl‐1.2‐benzazaborin) (2). Das gleiche Produkt entsteht erwartungsgemäß auch, wenn man die zur Bereitung von 1 nötige thermische Abspaltung von HCl aus C6F5B(NHC6H4OCH3)Cl in Gegenwart von Phenylacetylen ausführt. Bei Zusatz von Triäthylamin erhält man nicht 2, sondern unter Substitution von Chlorid am Boramidchlorid du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Therefore, triply bonded RE 13 ≡E 15 R is the next synthetic challenge. To the best of the authors' knowledge, only R 2 BN molecules that contain a B≡N triple bond have been experimentally demonstrated to exist [30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, triply bonded RE 13 ≡E 15 R is the next synthetic challenge. To the best of the authors' knowledge, only R 2 BN molecules that contain a B≡N triple bond have been experimentally demonstrated to exist [30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] However,studies on the synthesis of BN-doped PA Hs and basic azaborine building blocks,such as 2,1-borazaronaphthalene derivatives, have been reported only sparsely. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Considering the potential electronics applications of these compounds,t his lack of research is surprising.However,itcan be attributed to the challenges associated with incorporating boron and nitrogen atoms at specific framework positions and the difficulties in subsequently forming CC bonds that further expand aromatic p-conjugation. [34,35] While studying the electronic properties of pyrene (Figure 1a), we noticed that among various pyrene derivatives, Clar et al (1970) reported only one isomer of pyrene fused with four benzene rings ( Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] However,studies on the synthesis of BN-doped PA Hs and basic azaborine building blocks,such as 2,1-borazaronaphthalene derivatives, have been reported only sparsely. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Considering the potential electronics applications of these compounds,t his lack of research is surprising.However,itcan be attributed to the challenges associated with incorporating boron and nitrogen atoms at specific framework positions and the difficulties in subsequently forming CC bonds that further expand aromatic p-conjugation. [34,35] While studying the electronic properties of pyrene (Figure 1a), we noticed that among various pyrene derivatives, Clar et al (1970) reported only one isomer of pyrene fused with four benzene rings ( Figure 1b).…”
Section: Introductionmentioning
confidence: 99%